1939
DOI: 10.1192/bjp.85.355.256
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Ichthyosis, Idiocy, Infantilism and Epilepsy—The Syndrome of Rud

Abstract: To the student of mental deficiency the lower grades of oligophrenia offer endless opportunities for the exercise of his diagnostic acumen, and in this largely unexplored terrain there are doubtless many syndromes awaiting discovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

1966
1966
2001
2001

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Our patient's EEG was abnormal, with bisynchronous spike and slow-wave activity consistent with petit ma1 seizures for which he was being treated. Stewart (1939) reported generalized major motor seizures in his patients, but in other reports no clinical seizure activity occurred, although the EEGs were abnormal (York-Moore and Rundle 1962, Maldonado etal. 1975.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Our patient's EEG was abnormal, with bisynchronous spike and slow-wave activity consistent with petit ma1 seizures for which he was being treated. Stewart (1939) reported generalized major motor seizures in his patients, but in other reports no clinical seizure activity occurred, although the EEGs were abnormal (York-Moore and Rundle 1962, Maldonado etal. 1975.…”
Section: Discussionmentioning
confidence: 88%
“…Speech delay and impairment was also noted in patients with hearing-loss, but it occurred to a lesser degree in others with retardation but with normal hearing. Generalized polyneuropathy has been reported in three patients with this syndrome (Stewart 1939, Maldonado et a/. 1975, Larbrisseau and Carpenter 1982.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The medical literature has described various ichthyotic syndromes, most of which are combined with varied neurologic findings. They include Sjögren–Larsson syndrome, 3 Refsum syndrome, 4 Rud syndrome, 5 Laubenthal's syndrome, 6 Stewart's syndrome, 7 Conradi syndrome, 8 Tay's syndrome, 9 congenital hemidysplasia with ichthyosiform erythroderma and limb defects (CHILD) syndrome, 10 and other unnamed syndromes 11 13 . The neurologic abnormalities have included symptoms such as epilepsy, mental retardation, infantilism, spastic paresis, deafness, polyneuritis, and progressive cerebellar degeneration 6,14 …”
Section: Discussionmentioning
confidence: 99%
“…Musculoskeletal findings reported in patients with these syndromes have included partial gigantism, 5 dwarfism, 11,12 , 15 muscular atrophy, 7 arachnodactyly, 7 clinodactyly, 13 delayed epiphyseal closure, 16 limb defects, 10 shortened proximal limbs, 8 calcified stippling of the epiphysis, 8 congenital dislocation of the hips, 17 talipes equino varus, 16,18 pectus excavatum, 19 syndactyly, 20 short metacarpals, 4,21 scoliosis, 17,22 epiphyseal–metaphyseal dysplasia, 23 and delayed dentition 6 . Several authors have reported ichthyoses with musculoskeletal disorders, which are not accompanied by neurologic aberrations.…”
Section: Discussionmentioning
confidence: 99%